Electron-transporting phenazinothiadiazoles with engineered microstructure - Lindner, Benjamin; Paulus, Fabian; Appleton, Anthony L.; Schaffroth, Manuel; Engelhart, Jens U.; Schelkle, Korwin; Tverskoy, Olena; Rominger, Frank; Hamburger, Manuel; Bunz, Uwe H. F. (Journal of materials chemistry. C, Materials for optical and electronic devices, 2014)
Novel triisopropylsilyl-(TIPS)-alkynylated phenazinothiadiazoles were prepared by condensation of ortho-quinones and an alkynylated 5,6-diamino-2,1,3-benzothiadiazole. The targets show head-to-head dimerisation in the solid state, which, according to calculated transfer integrals should favor charge transport. The compounds form polycrystalline thin films when spin cast from solution. Two derivatives are attractive electron transporting materials with an average electron mobility μe in thin film transistors (TFT) of 0.07 cm2 V−1 s−1.
Gesehen am 19.10.2020